The use of the “kahoot!” Software as an instrument of formative assessment in integrated high school (Research, Society and Development, 2020)
Discussions about the use of games in the teaching-learning process are a current topic, especially with the growth of computerization in schools and the increasing presence of mobile devices in the possession of students. How to transform new technologies into teachers' allies instead of sources of distraction? How to enter the world of students of this digital generation, social networks and various applications? These questions are in school corridors and in current scientific articles. In this work, we use the Kahoot! with the objective of verifying the extent to which the tool assists in the process of formative evaluation of integrated high school students from a federal educational institution. Methodologically, we adopt a qualitative perspective for data analysis. The results show good acceptance by the students, increased attention and motivation in the classes, and the methodology was able to create a gamified and fun environment for the students, in addition to bringing a compilation of information to the student about the individual and collective performance of the class. We perceive limitations in terms of its applicability in the case of punctuated evaluations, greater difficulty in responding with the involvement of the mathematical operations competence, which may be more specific work in future works and adaptations of the method.